Rancangan Alat Bantu Pembelajaran IPA Materi Perubahan Cuaca 2 Musim Untuk Siswa SLB Bagian B Tunarungu Berbasis Multimedia - Sri Ela Dinasti; Diana Effendi (Universitas Islam Sumatera Utara, 2020)
Cicendo SLBN still uses conventional learning methods when learning science especially in the subject of 2-season weather change in grade 6 where educators still teach lesson through the blackboard and when there is lesson non-verbal, teaching educators only use writing with pictures that are not too explain how the lesson and this method are considered less attractive and can not be understood by students.The purpose of this study is to facilitate educators in delivering lesson to 6th grade deaf students and implementing the learning application to students in order to improve his interest in the lesson 2-season weather change and made it easier for them to understand the lesson. To finish this research, the writer uses qualitative research methods which will produce descriptive data such as interviews and observations. For system development methods using prototypes. The results of this study are multimedia-based learning applications for 2-season weather change.